Methodology of Islamic psychotheraphy in Islamic boarding school Suryalaya Tasik Malaya - Khairunnas Rajab (IAIN Salatiga, 2014)
Islamic Psychotherapy is a methodology that is based on the Quran andSunnah. The Quran and Sunnah are sources of knowledge. Islamic psychotherapyprovides solutions to mental disorder. Suryalaya Boarding school hasprovided guidance to patients who are addicted to drugs in order to be recovered.The Islamic psychotherapy model applied at the boarding school is theSufism-based approach. Sufism is a way to get closer to God. Through theapproach, drug-addicted patients can be cured. If the patients realize that Godanswers their prayers through worship, the sense of sinfulness and guiltinesswill gradually disappear. The boarding school has been implementing Islamicpsychotherapy of Qadiriyyah-Naqsyabandiyyah approach. Through the approach,the patients succeeded to be completely recovered. This article attempts toexplain the important roles of the school in treating patients suffering frommental disorder due to misuse of drugs.Psikoterapi Islam adalah sebuah metodologi yang berdasarkan al-Qur’an danal-Sunnah. Al-Qur’an dan al-Sunnah adalah sumber ilmu pengetahuan.Psikoterapi Islam memberikan solusi bagi orang-orang yang mengalamigangguan mental. Pondok Pesantren Suryalaya telah melakukan pembinaan terhadap pasien yang kecanduan narkotika. Model psikoterapi Islam yangditerapkan di pondok pesantren ini adalah psikoterapi dengan pendekatantasawuf. Melalui pendekatan Tasawuf pasien narkotika dapat dipulihkan.Tasawuf adalah upaya seseorang untuk mendekatkan diri kepada Tuhannya.Apabila pasien narkotika menyadari bahwa Allah mengabulkan doa-doa melaluiibadah, maka perasaan berdosa dan bersalah secara bertahap akan hilang.Pondok Pesantren Suryalaya selama ini telah menerapkan sebuah modelpsikoterapi Islam dengan pendekatan thariqat Qadiriyyah-Naqsyabandiyyah.Dengan Thariqat Qadiriyyah-Naqsyabandiyah pasien-pasien narkotika dapatdisembuhkan secara sempurna. Artikel ini berupaya menjelaskan peran pentingPondok Pesantren Suryalaya dalam penyembuhan pasien yang mengalamigangguan mental akibat penyalahgunaan narkotika.